(12-v)=-3

Simple and best practice solution for (12-v)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12-v)=-3 equation:


Simplifying
(12 + -1v) = -3

Remove parenthesis around (12 + -1v)
12 + -1v = -3

Solving
12 + -1v = -3

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -1v = -3 + -12

Combine like terms: 12 + -12 = 0
0 + -1v = -3 + -12
-1v = -3 + -12

Combine like terms: -3 + -12 = -15
-1v = -15

Divide each side by '-1'.
v = 15

Simplifying
v = 15

See similar equations:

| 4X+2Y=336 | | (2x-1)+(6x+2)+(5x+3)=180 | | -2/3-4/3=0 | | 3a+-b=6 | | 4x-2(-1)=4x-23(-5) | | y=3x+8-(12x) | | 81x^2=100x | | 15a^2-8=29a+6 | | 3264/5.10 | | 3x-2h=46 | | 6x+10+3x=118 | | 3n^2+12n-63=0 | | -4j+j= | | 4(2+8v)=-6v+8 | | 1a+3b=6 | | 6s+-8=18 | | (2x+4)(3x-3)=0 | | x-2.4=5.6 | | 3x^3+87x^2+162x=0 | | 5x+1-18= | | (7x+15)+(x+5)=180 | | .25(8-6x+12)= | | 15a^2-8=29a+9 | | 2x^3-21x^2+34x=0 | | 8x^3-3x^2-32x+12=0 | | 10+3x+2x=-45 | | 9+2y=y | | 9(x-1)=6(x+5) | | (3+w)w=w(7-w) | | 5j-j=12 | | x^2-50x+100=8400 | | 6x^3+26x^2-76x=0 |

Equations solver categories